Let's analyze Jason's work step-by-step:
-
Step 1: The original equation \( x^2 - 4x - 12 = 0 \) is correct.
-
Step 2: He factored the equation as \( (x - 6)(x + 2) = 0 \). To verify this, we can expand \( (x - 6)(x + 2) \):
\[ (x - 6)(x + 2) = x^2 + 2x - 6x - 12 = x^2 - 4x - 12 \]
This step is actually correct.
-
Step 3: From \( (x - 6)(x + 2) = 0 \), he correctly sets each factor to zero:
- \( x - 6 = 0 \) gives \( x = 6 \)
- \( x + 2 = 0 \) gives \( x = -2 \)
Here, he made a mistake in writing down the second solution. It should be \( x = -2 \), not \( x = 2 \).
-
Step 4: He states \( x = 6 \) or \( x = 2 \). This is incorrect because one of the solutions is wrong.
-
Step 5: Jason concludes that the solutions are \( {6, 2} \), which is incorrect.
Therefore, Jason's first mistake occurred in Step 3, where he incorrectly stated the second solution as \( x = 2 \) instead of the correct solution \( x = -2 \).